The Role of Vitamin C Supplementation in Preventing Severity Progression in Mild and Moderate COVID-19 Patients at Universitas Airlangga Hospital - Yoga Akbar Arifandi; Alfian Nur Rosyid; Danti Nur Indiastuti; Wiwin Is Effendi (Juxta: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga)
Introduction: Coronavirus disease (COVID-19) is an infectious disease that increases pro-oxidant elements and decreases antioxidants. Vitamin C functions as a potent antioxidant in humans due to its electron-donating properties. This study aimed to explain the impact of three distinct vitamin C supplementation dosages in preventing disease severity progression among mild and moderate COVID-19 patients.